Cardiac function in pregnant women with preeclampsia - Yerlikaya-Schatten, Gülen; Karner, Eva; Heinzl, Florian; Prausmüller, Suriya; Kastl, Stefan; Springer, Stephanie; Zilberszac, Robert (Frontiers in Cardiovascular Medicine, 2024)
IntroductionPreeclampsia (PE) is thought to be the consequence of impaired placental perfusion leading to placental hypoxia. While it has been demonstrated that PE may be a consequence of maternal cardiovascular maladaptation, the exact role of maternal cardiac function remains to be determined. This study sought to assess cardiac characteristics in pregnant women diagnosed with PE and to determine the possible relationship between PE, maternal cardiac changes/function, and NT-proBNP levels.MethodsThis was a retrospective analysis of 65 pregnant women diagnosed with PE who had an echocardiographic examination during pregnancy. Where available, NT-proBNP levels were analyzed. All patients underwent a comprehensive echocardiographic examination based on a standardized examination protocol.ResultsLeft ventricular size was within the normal range, and there was normal radial left ventricular function. Longitudinal contractility was impaired with a global longitudinal strain of −17.8% (quartiles −20.2 to −15.4). The cardiac index was in the normal range with a median of 3.2 ml/min/m2 (quartiles 2.6–4.0). The left atrium was of borderline size in longitudinal diameter [50 (44.8–54.3) mm], but within the normal range in volumetric index [27.3 (22.9–37.3) ml/m2]. Furthermore, mild left ventricular hypertrophy [septal thickness 12 (10–13) mm] and at least borderline elevated filling pressures with an E/e' ratio of 10.6 (8.5–12.9) were found. Maximal tricuspid regurgitation velocity [2.9 (2.5–3.3) m/s] and derived systolic pulmonary pressure [38 (29.5–44.5) mmHg] were borderline elevated. Regarding NT-proBNP levels, an increase in NT-proBNP levels correlated with a decrease in gestational age at delivery (p < 0.0002) and maternal cardiac changes. Obstetric characteristics showed a preterm rate of 71.43%, mostly due to maternal aggravation of PE or because of fetal signs of deprivation based on placental insufficiency. Neonatal deaths occurred in five cases (7.69%).ConclusionChanges in cardiac function in the context of hypertensive pregnancy diseases can be observed with regard to various echocardiographic parameters. Furthermore, there is a significant association between NT-proBNP levels and a decrease in gestational age at delivery in women with PE, which thus might be useful as a prognostic factor for the management of women with preeclampsia and changes in maternal cardiac function during pregnancy.